The Role of Grammatical Category Information in Spoken Word Retrieval - Palma Duràn, Carolina; Pillon, Agnesa (Frontiers in Psychology, 2011)
We investigated the role of lexical syntactic information such as grammatical gender and category in spoken word retrieval processes by using a blocking paradigm in picture and written word naming experiments. In Experiments 1, 3, and 4, we found that the naming of target words (nouns) from pictures or written words was faster when these target words were named within a list where only words from the same grammatical category had to be produced (homogeneous category list: all nouns) than when they had to be produced within a list comprising also words from another grammatical category (heterogeneous category list: nouns and verbs). On the other hand, no significant facilitation effect was detected when the target words had to be named within a homogeneous gender list (all masculine nouns) compared to a heterogeneous gender list (both masculine and feminine nouns). In Experiment 2, using the same blocking paradigm by manipulating the semantic category of the items, we found that naming times were significantly slower in the semantic category homogeneous in comparison with the semantic category heterogeneous condition. Thus semantic category homogeneity caused an interference, not a facilitation effect like grammatical category homogeneity. Finally, in Experiment 5, nouns in the heterogeneous category condition had to be named just after a verb (category-switching position) or a noun (same-category position). We found a facilitation effect of category homogeneity but no significant effect of position, which showed that the effect of category homogeneity found in Experiments 1, 3, and 4 was not due to a cost of switching between grammatical categories in the heterogeneous grammatical category list. These findings supported the hypothesis that grammatical category information could impact word retrieval processes in speech production, even when words are to be produced in isolation. They are discussed within the context of extant theories of lexical production.